(untitled) (Eurasian Journal of Philology Science and Education, 2021)
The research purpose is to study and analyze the multilingual language situation in the oil industry in Kazakhstan and determine the areas of use of the Kazakh-Russian-English trilingualism in this industry. The study showed that the expansion of the spheres of language use directly depends on the level of social and cultural development of the people, and to a certain extent also on its state structure and number. The development of various communication domains is reflected in the internal structure of the language. Each domain has its own specific characteristics. At present, the oil industry of Kazakhstan is served by three languages, and the oil industry of Kazakhstan can be called trilingual. Trilingualism is active in the following domains: oil production, oil record keeping and business communication, oil legislation, oil education, oil sciences, oil periodicals. Depending on the number of communication domains in the oil industry, a corresponding number of social functions appear in the languages that serve this industry. When studying the domains of communication and describing the current linguistic situation in the oil industry, various methods were used: theoretical and linguistic, including the analysis of linguistic, psycholinguistic, methodological literature, followed by analysis, generalization and description of the results and conclusions. The results and materials of the research can be used in the study of the characteristic features of the process of interaction of the Kazakh, Russian, English languages and its influence on the enrichment of each of them, as well as in the process of conducting scientific research on polylingualism with the participation of other languages.